2002
DOI: 10.1161/hs0102.100482
|View full text |Cite
|
Sign up to set email alerts
|

Altered Hemodynamic Responses in Patients After Subcortical Stroke Measured by Functional MRI

Abstract: Background and Purpose-Blood oxygenation level-dependent (BOLD) functional MRI (fMRI) is a promising method for defining brain recovery after stroke quantitatively. Applications thus far have assumed that the BOLD hemodynamic response in patients after stroke is identical to that in healthy controls. However, because of local vascular compromise or more diffuse vascular disease predisposing to infarction, this assumption may not be justified after stroke. We sought to test whether patients who have suffered a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 36 publications
3
111
1
Order By: Relevance
“…However, patients without significant large-vessel disease (e.g., Patient 1) also showed impaired BOLD signal, and patients with persistent ICA occlusion (e.g., Patient 6) or previous ICA surgery due to known large-vessel disease (e.g., Patient 9) showed a positive BOLD signal. Previous studies have also shown impaired vascular reserve capacity in patients with suspected small-vessel disease due to hypertension (Ficzere et al, 1997), as well as lower BOLD response in patients with lacunar strokes (Pineiro et al, 2002) and/or white matter degeneration (Hund-Georgiadis et al, 2003), arguing in favor of an impairment of BOLD reactivity in both large-and small-vessel disease.…”
Section: Hemometabolic Uncouplingmentioning
confidence: 97%
“…However, patients without significant large-vessel disease (e.g., Patient 1) also showed impaired BOLD signal, and patients with persistent ICA occlusion (e.g., Patient 6) or previous ICA surgery due to known large-vessel disease (e.g., Patient 9) showed a positive BOLD signal. Previous studies have also shown impaired vascular reserve capacity in patients with suspected small-vessel disease due to hypertension (Ficzere et al, 1997), as well as lower BOLD response in patients with lacunar strokes (Pineiro et al, 2002) and/or white matter degeneration (Hund-Georgiadis et al, 2003), arguing in favor of an impairment of BOLD reactivity in both large-and small-vessel disease.…”
Section: Hemometabolic Uncouplingmentioning
confidence: 97%
“…These include individual differences in the size and location of veins (Bandettini and Wong 1997;Cohen, et al 2004), extracranial arterial disease (Hamzei, et al 2003;Rother, et al 2002), small vessel cerebral disease (Pineiro, et al 2002), pulse or respiration differences (Dagli, et al 1999;, hematocrit concentrations (Levin, et al 2001), baseline CBF (Cohen, et al 2002). Several studies have also revealed that medications and food intake can affect the BOLD signal.…”
Section: Introductionmentioning
confidence: 99%
“…However, application of this approach to other populations, such as aging and patient populations, has been a constant challenge [D'Esposito et al, 2003]. We expect that localization of task-related activation would be particularly sensitive to the fixed-HRF assumption, at higher association brain regions, and at subject populations, in which untypical HRFs are commonly observed [Pineiro et al, 2002;Rother et al, 2002;Hamzei et al, 2003]. Under theses circumstances, we predict that the information-theoretic method may be superior over the model based GLM analysis.…”
Section: Discussionmentioning
confidence: 99%